2023
DOI: 10.3390/su151813996
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Variation and Future Predictions of Soil Salinization in the Werigan–Kuqa River Delta Oasis of China

Baozhong He,
Jianli Ding,
Wenjiang Huang
et al.

Abstract: Soil salinization is a serious global issue; by 2050, without intervention, 50% of the cultivated land area will be affected by salinization. Therefore, estimating and predicting future soil salinity is crucial for preventing soil salinization and investigating potential arable land resources. In this study, several machine learning methods (random forest (RF), Light Gradient Boosting Machine (LightGBM), Gradient Boosting Decision Tree (GBDT), and eXtreme Gradient Boosting (XGBoost)) were used to estimate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…It is situated in the alluvial and diluvial plain zone at the southern foothills of the Tianshan Mountains in the central-northern part of the Tarim Basin, between 81 • 28 ′ 30 ′′ E and 84 • 05 ′ 06 ′′ E longitude, and 39 • 29 ′ 51 ′′ N and 42 • 38 ′ 01 ′′ N latitude. The elevation of the plain area is between 976 and 1030 m, belonging to a continental warm temperate arid climate [41]. The average annual temperature is 11.6 • C, with cold winters, long frost-free periods, and scarce precipitation.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…It is situated in the alluvial and diluvial plain zone at the southern foothills of the Tianshan Mountains in the central-northern part of the Tarim Basin, between 81 • 28 ′ 30 ′′ E and 84 • 05 ′ 06 ′′ E longitude, and 39 • 29 ′ 51 ′′ N and 42 • 38 ′ 01 ′′ N latitude. The elevation of the plain area is between 976 and 1030 m, belonging to a continental warm temperate arid climate [41]. The average annual temperature is 11.6 • C, with cold winters, long frost-free periods, and scarce precipitation.…”
Section: Study Areamentioning
confidence: 99%
“…Referring to the "Yunnan Province Forest Resource Planning and Design Survey Operation Rules", the slope was divided into six levels and the aspect was divided into nine directions [45,46]. Using the reclassification tool in ArcGIS, the slope was divided into six categories (in degrees): gentle slope (0-5), mild slope (6)(7)(8)(9)(10)(11)(12)(13)(14)(15), moderate slope (16)(17)(18)(19)(20)(21)(22)(23)(24)(25), steep slope (26)(27)(28)(29)(30)(31)(32)(33)(34)(35), sharp slope (36)(37)(38)(39)(40)(41)(42)(43)(44)(45), and dangerous slope (≥46). The remaining six variables were converted from continuous to categorical using the natural break point classification method (Table 1).…”
Section: Data Preprocessingmentioning
confidence: 99%
“…These studies show that the L8 satellite image is more effective for monitoring soil salinity than the S2 image 13 , 18 20 . Also, researchers have employed RF 21 , XGBoost 22 , Decision Tree (DT) 23 , and SVR 24 , 25 as predictive tools in their investigations, and these models consistently demonstrated robust and reliable performance in the context of soil salinity prediction.…”
Section: Introductionmentioning
confidence: 99%
“…The soil salinity content and characteristics directly affect crop growth, soil carbon sequestration, and ecosystem security [5][6][7]. The salinity in the profiles of desertsierozem soils varies greatly during irrigated maturation, and farmed desert-sierozem soils show a reverse soil salinity succession process, i.e., the salts in the soils gradually decrease with an increasing duration of cultivation [8]. It was found that the longer the cultivation period, the more significant the reverse change in soil salinity, and the earlier the farmland is removed from the influence of the groundwater table, the earlier the reverse salinity succession process occurs and the more complete the soil desalination is [9].…”
Section: Introductionmentioning
confidence: 99%